2015
DOI: 10.1016/j.jet.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment risk and wage differentials

Abstract: Workers in less secure jobs are often paid less than identical-looking workers in more secure jobs. We show that this lack of compensating differentials for unemployment risk can arise in equilibrium when all workers are identical and firms differ only in job security (i.e. the probability that the worker is not sent into unemployment). In a setting where workers search for new positions both on and off the job, the worker's marginal willingness to pay for job security is endogenous: it depends on the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…One of the most significant challenges faced by low-wage workers is the risk of job loss. Research has found that low-wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, 2017;Lucifora & Salverda, 2009;Pinheiro & Visschers, 2015;Stewart, 2007). Existing evidence also suggests that low-wage workers have shorter job tenures (Lane, 2000) and that engagement in low-wage employment can be a trap for many workers, making the transition from low-wage work to high-wage work difficult (Lucifora & Salverda, 2009;Mason & Salverda, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant challenges faced by low-wage workers is the risk of job loss. Research has found that low-wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, 2017;Lucifora & Salverda, 2009;Pinheiro & Visschers, 2015;Stewart, 2007). Existing evidence also suggests that low-wage workers have shorter job tenures (Lane, 2000) and that engagement in low-wage employment can be a trap for many workers, making the transition from low-wage work to high-wage work difficult (Lucifora & Salverda, 2009;Mason & Salverda, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pinheiro and Visschers (2015) have a job ladder model where the jobs at the bottom of the ladder have the highest probability of unemployment associated with them. Neither paper studies displaced worker earnings.…”
mentioning
confidence: 99%
“…Jarosch (2015) also highlights the importance of heterogeneity in job stability to account for observed earnings losses. While heterogeneity in job stability arises as a bargaining outcome between employers and workers in Jung and Kuhn (2018), we follow Pinheiro and Visschers (2015) and Jarosch (2015) and introduce this heterogeneity in reduced form to the job-offer distribution. 1 Guvenen et al (2019) explore life-cycle earnings dynamics and document large heterogeneity in life-cycle nonemployment spells.…”
Section: Related Literaturementioning
confidence: 99%